2015
DOI: 10.3892/or.2015.4221
|View full text |Cite
|
Sign up to set email alerts
|

Promoting roles of the secreted frizzled-related protein 2 as a Wnt agonist in lung cancer cells

Abstract: The secreted frizzled-related protein 2 (SFRP2) plays a pivotal role in the Wnt pathway, however, it functions as an agonist or an antagonist is still controversial. We profiled SFRP2 expression in several lung cancer cell lines, and found that A549 and 95-D exhibited the lowest and the highest level of SFRP2, respectively. Then we employed the SFRP2-overexpressing plasmid and siRNA to transfect A549 and 95-D cells, respectively. Through MTT assays, we found that SFRP2 knockdown inhibited cell proliferation, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 28 publications
(30 reference statements)
5
17
0
Order By: Relevance
“…To clarify whether SFRP2 increases or decreases as tumors progress, we previously found that SFRP2 signal intensity increased as a function of tumor volume using SFRP2-targeted molecular imaging of a mouse tumor in vivo [33]. Other studies confirmed our observation showing that overexpression of SFRP2 increases angiogenesis and tumor growth in vitro and in vivo , [8,9,4,6,34,1,7,2,3]. Furthermore, antagonizing SFRP2 with a monoclonal antibody inhibits tumor growth in vivo [10], which establishes the preponderance of evidence that SFRP2 stimulates, rather than suppresses, tumor growth.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…To clarify whether SFRP2 increases or decreases as tumors progress, we previously found that SFRP2 signal intensity increased as a function of tumor volume using SFRP2-targeted molecular imaging of a mouse tumor in vivo [33]. Other studies confirmed our observation showing that overexpression of SFRP2 increases angiogenesis and tumor growth in vitro and in vivo , [8,9,4,6,34,1,7,2,3]. Furthermore, antagonizing SFRP2 with a monoclonal antibody inhibits tumor growth in vivo [10], which establishes the preponderance of evidence that SFRP2 stimulates, rather than suppresses, tumor growth.…”
Section: Discussionsupporting
confidence: 78%
“…The preponderance of in vivo evidence supports that SFRP2 stimulates tumor growth. Gain of function studies have shown that SFRP2 strongly promotes tumor growth of intracranial glioma [1], renal cell carcinoma [2], lung cancer [3], melanoma [4], and osteosarcoma [5]. Overexpression of transfected SFRP2 in MCF7 breast adenocarcinoma cells increased their resistance to apoptotic signals in vitro [6].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the anti-invasive effects of DMTreC14 were observed at low concentrations (40 μM) without affecting growthinhibition. Actin cytoskeleton dynamics, such as lamellipodia and filopodia formation on the surface of tumor cells plays an important role in the invasion and migration into the surrounding tissue [18][19][20][21][22]. The treatment with DMTreC14 drastically inhibited the filopodia formation in A549 cells.…”
Section: Discussionmentioning
confidence: 99%
“…By the way, filopodia formation on the surface of tumor cells plays an important role in the invasion and migration into the surrounding tissue [18][19][20]. Accordingly, the suppression effects of DMTreC14 on the filopodia formation of A549 cells were observed by confocal laser microscopy.…”
Section: Suppression On Migration Of A549cells By Dntrec14mentioning
confidence: 99%
“…The antimigration effects of HL were scrutinized at low concentrations (200 μM) without affecting growth-inhibition below IC 50 values (200 μM). Additionally, pseudopodium development on the exterior of tumour cells has a chief responsibility in the invasion and migration into the neighbouring tissue [18][19][20]. The suppression actions of HL on the pseudopodium formation of MCF-7 cells were scrutinised by using confocal laser microscopy ( Figure 4).…”
Section: Suppression Effects On Migration Of Mcf-7 Cells By Hlmentioning
confidence: 99%